The Ecology of Acidobacteria: Moving beyond Genes and Genomes - Kielak, Anna M.; Barreto, Cristine C.; Kowalchuk, George A.; van Veen, Johannes A.; Kuramae, Eiko E. (Frontiers in Microbiology, 2016)
The phylum Acidobacteria is one of the most widespread and abundant on the planet, yet remarkably our knowledge of the role of these diverse organisms in the functioning of terrestrial ecosystems remains surprisingly rudimentary. This blatant knowledge gap stems to a large degree from the difficulties associated with the cultivation of these bacteria by classical means. Given the phylogenetic breadth of the Acidobacteria, which is similar to the metabolically diverse Proteobacteria, it is clear that detailed and functional descriptions of acidobacterial assemblages are necessary. Fortunately, recent advances are providing a glimpse into the ecology of members of the phylum Acidobacteria. These include novel cultivation and enrichment strategies, genomic characterization and analyses of metagenomic DNA from environmental samples. Here, we couple the data from these complementary approaches for a better understanding of their role in the environment, thereby providing some initial insights into the ecology of this important phylum. All cultured acidobacterial type species are heterotrophic, and members of subdivisions 1, 3, and 4 appear to be more versatile in carbohydrate utilization. Genomic and metagenomic data predict a number of ecologically relevant capabilities for some acidobacteria, including the ability to: use of nitrite as N source, respond to soil macro-, micro nutrients and soil acidity, express multiple active transporters, degrade gellan gum and produce exopolysaccharide (EPS). Although these predicted properties allude to a competitive life style in soil, only very few of these predictions have been confirmed via physiological studies. The increased availability of genomic and physiological information, coupled to distribution data in field surveys and experiments, should direct future progress in unraveling the ecology of this important but still enigmatic phylum.